Emergence of new Salmonella Enteritidis phage types in Europe? Surveillance of infections in returning travellers. - Nygård, K; de Jong, B; Guerin, P; Andersson, Y; Olsson, A; Giesecke, J (BioMed Central, 2004)
BACKGROUND: Among human Salmonella Enteritidis infections, phage type 4 has been the dominant phage type in most countries in Western Europe during the last years. This is reflected in Salmonella infections among Swedish travellers returning from abroad. However, there are differences in phage type distribution between the countries, and this has also changed over time. METHODS: We used data from the Swedish infectious disease register and the national reference laboratory to describe phage type distribution of Salmonella Enteritidis infections in Swedish travellers from 1997 to 2002, and have compared this with national studies conducted in the countries visited. RESULTS: Infections among Swedish travellers correlate well with national studies conducted in the countries visited. In 2001 a change in phage type distribution in S. Enteritidis infections among Swedish travellers returning from some countries in southern Europe was observed, and a previously rare phage type (PT 14b) became one of the most commonly diagnosed that year, continuing into 2002 and 2003. CONCLUSIONS: Surveillance of infections among returning travellers can be helpful in detecting emerging infections and outbreaks in tourist destinations. The information needs to be communicated rapidly to all affected countries in order to expedite the implementation of appropriate investigations and preventive measures.